2009
DOI: 10.1371/journal.pone.0005634
|View full text |Cite
|
Sign up to set email alerts
|

Control of Vertebrate Skeletal Mineralization by Polyphosphates

Abstract: BackgroundSkeletons are formed in a wide variety of shapes, sizes, and compositions of organic and mineral components. Many invertebrate skeletons are constructed from carbonate or silicate minerals, whereas vertebrate skeletons are instead composed of a calcium phosphate mineral known as apatite. No one yet knows why the dynamic vertebrate skeleton, which is continually rebuilt, repaired, and resorbed during growth and normal remodeling, is composed of apatite. Nor is the control of bone and calcifying cartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 83 publications
3
148
0
Order By: Relevance
“…An elemental analysis of the mice vesicles shows that the Ca/P ratio is below 1, implying that the disordered phase is rich in phosphate and could possibly be a polyphosphate, as has been suggested by Omelon et al [53] based on biochemical evidence and in situ identification within resorbing bone and mineralizing cartilage. We do not know how the mineral in the intracellular vesicles is transported to the extracellular space.…”
Section: Broader Implications Of a Transient Precursor Phase Strategymentioning
confidence: 66%
“…An elemental analysis of the mice vesicles shows that the Ca/P ratio is below 1, implying that the disordered phase is rich in phosphate and could possibly be a polyphosphate, as has been suggested by Omelon et al [53] based on biochemical evidence and in situ identification within resorbing bone and mineralizing cartilage. We do not know how the mineral in the intracellular vesicles is transported to the extracellular space.…”
Section: Broader Implications Of a Transient Precursor Phase Strategymentioning
confidence: 66%
“…Nucleation theory has been used to explain bone apatite formation because extracellular fluid is sufficiently saturated with respect to calcium and phosphate [perhaps stored as calciumpolyphosphate complexes (30)] to allow for mineral formation (31). However, recent insights into the role of amorphous mineral precursors in bone mineralization (3), and our and other's (12) observations of intracellular calcium and phosphorus-containing vesicles, suggests that active transport of mineral from the intrato the extracellular space may play a role in bone apatite formation.…”
Section: Resultsmentioning
confidence: 99%
“…13 We suggested that polyP could be involved in this increase of Pi; polyP is an energy-rich polymer consisting of up to several hundreds of phosphate residues. 14,15 There are only a few studies concerning the occurrence of polyP in animals; they are widely distributed and can be localized in the cell in a flexible, oriented, and relatively stable form, but also used in response to a wide variety of metabolic needs as a source of energy. These findings could have important consequences in clinical practice.…”
Section: Discussionmentioning
confidence: 99%